Landscape Heritage Protection and Perception in Urban Fringe Area: the Case of southern Part of Warsaw - Kupidura, Adrianna (European Spatial Research and Policy, 2015)
The inhabitants and local governments may treat landscape heritage resources as a cumbersome legacy, which disrupts development, or may see its potential, which may serve as the cornerstone for building a sense of local identity. These issues shall be of special importance in the case of areas located on the outskirts of cities, which are subject to strong urbanization pressure. New inhabitants of such areas often know nothing about the past and history of the landscape in which they have decided to live. This article presents two approaches to landscape heritage that can be observed in the southern outskirts of Warsaw. It presents the landscape heritage protection and management policy in those areas, as well as the perception of the elements of this heritage by the local community.